Sandwiching analytes with structurally diverse plasmonic nanoparticles on paper substrates for surface enhanced Raman spectroscopy. Issue 56 (11th October 2019) - Lartey, Jemima A.; Harms, John P.; Frimpong, Richard; Mulligan, Christopher C.; Driskell, Jeremy D.; Kim, Jun-Hyun
Abstract : Systematic combination of plasmonic nanoparticles on a paper-based substrate introduces SERS-based signal-enhancement environments via interparticle coupling and hot spots. Abstract : This report describes the systematic combination of structurally diverse plasmonic metal nanoparticles (AgNPs, AuNPs, Ag core–Au shell NPs, and anisotropic AuNPs) on flexible paper-based materials to induce signal-enhancing environments for surface enhanced Raman spectroscopy (SERS) applications. The anisotropic AuNP-modified paper exhibits the highest SERS response due to the surface area and the nature of the broad surface plasmon resonance (SPR) neighboring the Raman excitation wavelength. The subsequent addition of a second layer with these four NPs ( e.g., sandwich arrangement) leads to the notable increase of the SERS signals by inducing a high probability of electromagnetic field environments associated with the interparticle SPR coupling and hot spots. After examining sixteen total combinations, the highest SERS response is obtained from the second layer with AgNPs on the anisotropic AuNP paper substrate, which allows for a higher calibration sensitivity and wider dynamic range than those of typical AuNP–AuNP arrangement. The variation of the SERS signals is also found to be below 20% based on multiple measurements (both intra-sample and inter-sample). Furthermore, the degree of SERS signal reductions for the sandwiched analytes is notably slow, indicating their increased long-term stability. The optimized combination is then employed in the detection of let-7f microRNA to demonstrate their practicability as SERS substrates. Precisely introducing interparticle coupling and hot spots with readily available plasmonic NPs still allows for the design of inexpensive and practical signal enhancing substrates that are capable of increasing the calibration sensitivity, extending the dynamic range, and lowering the detection limit of various organic and biological molecules.